OPTIMALISASI TAMBAK UDANG DI TAMBAK UDANG INTENSIF LABUHAN LOMBOK DALAM MENINGKATKAN EKONOMI MASYARAKAT DI LABUHAN LOMBOK, PRINGGABAYA LOMBOK TIMUR - Ramadhan, Ananda Fadhil; Sudirman, Muhammad; Scabra, Andre Rachmat (Jurnal Wicara, 2024)
Labuhan Lombok Village is a village that has quite good potential in economic terms. This village excels in the fisheries sector, both marine fisheries and aquaculture, as well as agriculture with rice, corn and horticulture crops. The rich social culture with local wisdom and the tradition of mutual cooperation also becomes an attraction. The beautiful coastal environment with mangrove and coral reef conservation and sustainable agriculture are the ecological strengths of this village. Labuhan Lombok Village has the potential to become a model of sustainable and highly competitive rural development. This village is known as a strategic coastal village. The majority of residents work as fishermen and farmers, while others are involved in trade, services and home industry. This village has several promising tourism potentials, especially because of its natural beauty and beaches. The level of community education tends to increase with the existence of schools that provide primary to secondary education, and community social life is based on mutual cooperation and togetherness. In shrimp cultivation activities in shrimp ponds, the intention is also to involve the community as a permit place so that the pond runs smoothly during cultivation activities. The company's goal of involving the community is also to increase the prosperity and welfare of the surrounding community and to play a role in providing opportunities for the surrounding community and to improve the economy. Apart from that, the company also carries out social activities as a form of concern for the community such as mutual cooperation, sharing takjil, social service, tadarusan, and fasting together.